Folate/homocysteine phenotypes and MTHFR 677C>T genotypes are associated with serum levels of monocyte chemoattractant protein-1. - SCOTT, JOHN MARTIN (Elsevier, 2009)
Monocyte chemoattractant protein-1 (MCP-1) is a chemokine that recruits monocytes into the subendothelial cell layer in atherosclerotic lesions. Elevated homocysteine (hyperhomocysteinemia), which is usually associated with low-folate status, is a known risk factor for many pathologies with inflammatory etiologies. The present study was undertaken to examine whether there are associations between MCP-1 concentrations and folate/Hcy phenotype or methylenetetrahydrofolate reductase (MTHFR) 677C>T genotype in healthy young adults. In females, MCP-1 concentrations were positively correlated with Hcy and negatively correlated with both serum and red blood cell folate; female smokers and MTHFR 677T carriers had particularly elevated MCP-1 concentrations. Similar relationships were not seen in males. These findings may have implications for understanding the female predominance observed for a range of autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis.
PUBLISHED
Keywords: Immunology